ISLAMIC EDUCATION IN RESPONSE TO THE CHALLENGES OF EDUCATION IN INDONESIA - Achmad Asrori; Sunarto Sunarto (Pascasarjana IAIN Metro, 2021)
In addition to playing a role in preparing humans to enter the future, education also has a relationship with social transformation, and vice versa, various patterns of the education system describe the patterns, traditions, social culture of the existing society. So what is important to note is that an education system is built to carry out the